Rodrigo García, Gabo y Mercedes: una despedida. Bogotá: Alfaguara. Random House Literature. 2021, 104 pages - López-González, Rosendo; Ramírez-Valencia, Astrid (Visión electrónica, 2021)
Rodrigo García, Gabo y Mercedes